Analysis of Determinants of Local Own-Source Revenue of Bali Province: A Panel Data Approach - Wahyu Tri Wibowo; Nolla Billa Nasokha; Rifki Khoirudin (Universitas Ahmad Dahlan, Yogyakarta, 2026)
This study examines the impact of economic growth, foreign direct investment (FDI), local expenditure, and population on local own-source revenue (PAD) in Bali Province from 2012 to 2023. Employing a quantitative approach with panel data from nine districts/cities, the study applies Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). The research contributes to the existing literature in three novel ways: first, it is the pioneering study examining PAD determinants in a tourism-dependent economy during post-COVID-19 recovery period; second, it provides comprehensive empirical evidence on the asymmetric effects of population growth on regional revenue in tourism-centric regions; and third, it introduces an integrated analytical framework combining macro-fiscal and demographic variables for regional revenue analysis. Based on the Chow, Hausman, and Lagrange Multiplier tests, CEM was selected as the most appropriate model, with three variables significant at 1% level. The analysis reveals that FDI and local expenditure exert significant positive effects on PAD, whereby each unit increase in FDI raises PAD by 14.53% and each Rp 1 increase in local expenditure increases PAD by 103.69%. Conversely, population has a significant negative effect, with each additional person decreasing PAD by 75.71%, while economic growth exhibits no significant influence. The model explains 79.88% of the variation in PAD, with the remaining 22.12% influenced by external factors. To optimize development, several key strategies are recommended, including economic diversification beyond tourism, simplifying investment licensing procedures, optimizing productive regional spending, and improving human resource quality through market-oriented vocational education.